The strategic response of banks to macroprudential policies: Evidence from mortgage stress tests in Canada - Robert Clark; Shaoteng Li (Queen's University, Department of Economics, 2020)
Following the crisis, macroprudential regulations targeting mortgage-market vulnerabilities were widely adopted, their success often depending on intermediaries' responses. We show that Canadian banks behaved strategically to limit the potency of recently implemented mortgage stress tests, requiring borrower qualification based on the mode of 5-year rates posted by the Big 6 banks rather than transaction rates. The government aimed to cool credit markets, but since many mortgages are government-insured, Big 6 interests were not aligned. Using DiD comparing changes in 5-year spreads with 3-year spreads, unaffected by the policy, we find rates were lowered encouraging continued borrowing, muting the tests' impact.
Keywords: 330; macroprudential regulation; credit supply; mortgage market; mortgage stress tests; rate-benchmark manipulation